2016
DOI: 10.1637/11304-101815-reg
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Presence in European Starlings Inhabiting Commercial Piggeries in South Australia

Abstract: The majority of bacterial diarrhea-causing illnesses in domestic pigs result from infection with Escherichia coli, Salmonella spp., or Campylobacter spp. These bacterial enteropathogens also correspond with the most-common bacteria isolated from wild birds. Additionally, viral pathogens such as avian influenza virus (AIV), West Nile virus (WNV, including Kunjin disease), and Newcastle disease virus (NDV) may also be carried and transmitted by birds in Australia. Introduced European starlings (Sturnus vulgarus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…A number of field studies have provided evidence that wild caught European starlings can be naturally infected or exposed to IAVs [19,[25][26][27][28][29][30][31]. However, in aggregate these studies suggest that starlings are not frequently infected or exposed to IAVs [32][33][34]. The relatively low seroprevalence observed in these studies might be partially explained by the relative transience of detectable antibodies demonstrated in our study.…”
Section: Plos Pathogenscontrasting
confidence: 43%
“…A number of field studies have provided evidence that wild caught European starlings can be naturally infected or exposed to IAVs [19,[25][26][27][28][29][30][31]. However, in aggregate these studies suggest that starlings are not frequently infected or exposed to IAVs [32][33][34]. The relatively low seroprevalence observed in these studies might be partially explained by the relative transience of detectable antibodies demonstrated in our study.…”
Section: Plos Pathogenscontrasting
confidence: 43%
“…However, outdoor farming may increase due to public demand for more ethical and natural animal production and higher quality meat products (Jori et al, 2017, Murrell, 2016. Especially, pigs with outdoor access in areas of high-density wild boar populations should apply biosecurity practices to prevent contact between them and wild boars (Pearson et al, 2016).…”
Section: Control Of Foodborne Zoonotic Pathogens From Wild Boarsmentioning
confidence: 99%
“…In cattle, most strains are non-pathogenic but some cause economically important disease [12]; cows also carry strains pathogenic to humans. In pigs, some strains cause economically important disease [13]. To the extent that starlings can spread these bacteria among livestock, pets, or directly to humans, an interest in their role in disease dynamics is warranted.…”
Section: Escherichia Colimentioning
confidence: 99%
“…A large variety of strains have been cultured or identified from European starlings. A study in Australia [13] identified 5 different strains from 6 individuals (S. enterica enterica serovar Kottbus, S. enterica enterica serovar Muenster, S. enterica enterica serovar Bredeney, S. enterica enterica serovar Anatum, S. enterica enterica serovar Oranienburg.) Carlson et al [31] identified 5 different strains from 100 individuals, and all strains were recovered both from gastrointestinal cultures and cultures made from external washes.…”
Section: Salmonellamentioning
confidence: 99%
See 1 more Smart Citation